Developmental analysis of bone marrow neutrophils reveals populations specialized in expansion, trafficking, and effector functions - Kwok, Immanuel Weng Han (2019)
Neutrophils are specialized innate cells that require constant replenishment from proliferative bone marrow (BM) precursors as a result of their short half-life. Although it is established that neutrophils are derived from the granulocyte-macrophage progenitor (GMP), the differentiation pathways from GMP to functional mature neutrophils are poorly defined. Using mass cytometry (CyTOF) and cell-cycle-based analysis, we identified three neutrophil subsets within the BM: a committed proliferative neutrophil precursor (preNeu) which differentiates into non-proliferating immature neutrophils and mature neutrophils. Transcriptomic profiling and functional analysis revealed that preNeu require the C/EBPε transcription factor for their generation from the GMP, and their proliferative program is substituted by a gain of migratory and effector function as they mature. preNeus expand under microbial and tumoral stress, and immature neutrophils are recruited to the periphery of tumor-bearing mice. In summary, our study identifies specialized BM granulocytic populations that ensure supply under homeostasis and stress responses.